Novel Hollow Graphene Flowers Synthesized by Cu‐Assisted Chemical Vapor Deposition. Issue 16 (13th June 2018) - Yang, Jie; Qian, Xihui; Li, Hao; Wang, Huaping; Xue, Xudong; Cai, Le; Hu, PingAn; Yu, Gui
Abstract: Novel hollow graphene flowers (HGFs) are synthesized by a Cu‐assisted chemical vapor deposition. Multilayer graphene films and vertical‐oriented graphene nanosheets are grown on hollow silica spheres successively by controlling the CH4 /H2 flow and growth time. After graphene growth, HSS templates are removed to achieve HGFs. The π‐conjugated systems and unique morphology of HGFs lead to apparent adsorption ability for dyes and phenol molecules. This work provides a facile way to produce unique hollow structure graphene with massive edges for different applications in the future. Abstract : Novel hollow graphene flowers synthesized by a Cu‐assisted chemical vapor deposition are reported for the first time. Multilayer graphene films and vertical‐oriented graphene nanosheets are grown on hollow silica spheres successively by controlling the CH4 /H2 flow and growth time. The hollow graphene flower, comprising of a hollow graphene sphere and abundant graphene petals, exhibits great potential in energy and environment applications.